Implementation of Ergonomic Elderly Gymnastics Decreases Complaints of Elderly Joint Pain in Peguyangan Denpasar – Bali - Nengah, Ariati; Ida Ayu Eka , Padmiari; Sugiani, Pande Putu Sri; Arjani, Ida Ayu Made Sri (Universitas Atma Jaya Yogyakarta, 2022)
The body change in the elder age, such as regressions in physical, psychological, and social that, can give an impact on health problems. Exercising sports such as elderly gymnastics has been proven to prevent or slow down functional loss. Ergonomic elderly gymnastics can improve physical fitness, improve the body's composition and increase the elderly bone mass had also been applied in Banjar Kepuh Kepuh Peguyangan aimed to reduce pain complaints of the elderly. The implementation of ergonomic elderly gymnastics involves 25 elderly people and pre-elderly. Gymnastics activities were carried out for four weeks with the frequency of exercises three times every week. Pre-data retrieval was carried out before the execution of exercises, and the Post data was taken after four weeks of elderly gymnastics. Data taken include sample identity and pain complaints using the Nordic Body Map questionnaire. The differences between before and after treatment were analyzed by the Different Wilcoxon test at the 5% confidence level (α = 0.05). After regularly exercising for four weeks, there was a decrease in pain complaints by 22.8%, with the category mild pain. The Difference test of Wilcoxon had a significant difference in the sample pain complaints (P <0.05) before and after the execution of gymnastics for four weeks. It was recommended that elderly gymnastics activities be carried out regularly because gymnastics sports positively impact the body's health and fitness.